Climate adaptation management and institutional erosion: insights from a major Canadian port. Issue 4 (21st March 2019) - Ng, Adolf K. Y.; Monios, Jason; Zhang, Huiying
Abstract : This paper performs an institutional analysis of the adaptation to climate change by ports, through a case study of the port of Vancouver, Canada. While previous literature has demonstrated the value of informal institutions for filling gaps left by formal institutions, the role of failed informal institutions has received less attention. Our analysis reveals how, in the case of an unprecedented challenge like climate adaptation, relying on informal institutions with less agency can actually erode the strength of existing institutions in a form of negative institutional plasticity. In this case, emerging polycentric governance was unsuccessful, unable to construct clearly demarcated responsibilities due to impedance by the path dependence of the current federalist system. The latter works well for traditional infrastructure investments with a closed pool of stakeholders, but not for ports where multiple scales of embeddedness, both horizontally and vertically, produce a collective action problem with no mechanism for resolution.